Pengaturan Hukuman Kebiri Kimia dan Pemasangan Alat Pendeteksi Elektronik dalam Perspektif Undang-Undang Dasar Negara Republik Indonesia Tahun 1945 - Talita Costanza; Hatarto Pakpahan (University of Merdeka Malang, 2021)
Punishments for chemical castration and the installation of electronic detectors are additional penalties that can be imposed for perpetrators of sexual violence against children. This additional penalty complements the weighting of the basic sentence (death penalty, life imprisonment, or imprisonment of at least 10 years and a maximum of 12 years) for perpetrators of sexual violence against children with more than one child victim. This research examines the regulation of chemical castration punishment and the installation of electronic detection devices in the perspective of the 1945 Constitution and from the perspective of criminal law in Indonesia. This study uses a normativejuridical approach. This approach focuses on examining laws and regulations which is carried out by examining all laws and regulations related to the legal issue that is being handled. The results of this study are chemical castration punishment and the installation of electronic detection devices for perpetrators of sexual violence against children, contrary to the values in the 1945 Constitution which uphold the dignity of all Indonesian citizens apart from the very negative impact, namely dangerous diseases that will appear in the body of the perpetrator as a result of the sentence. In addition, this punishment is not in line with the objectives of criminal law in Indonesia, because the sexual arousal possessed by perpetrators of sexual violence against children willstill exist because the effects of chemical castration (injection of anti-androgen fluid) are not permanent and thus ineffective in its application.